2022
DOI: 10.2147/opth.s381503
|View full text |Cite
|
Sign up to set email alerts
|

Faricimab for Treatment-Resistant Diabetic Macular Edema

Abstract: To assess the short-term outcomes in treatment-resistant diabetic macular edema (DME) patients changed from intravitreal aflibercept (IVA) to intravitreal faricimab (IVF). Methods: A retrospective review was undertaken on DME subjects receiving IVA therapy at a single private practice. Patients were separated into study and control cohorts. Both study and control patients had received more than or equal to six IVA injections during the preceding 12 months, more than or equal to four IVA injections during the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 14 publications
2
26
1
Order By: Relevance
“…A recent study by Elnahry et al found that OCT and OCT-angiography markers, such as a higher CSFT and a smaller foveal avascular zone area, as well as increased vessel densities in superficial parafovea and deep fovea, were associated with a better response to monthly intravitreal bevacizumab injections than in non-responders [ 24 ]. Patients who do not respond adequately to standard anti-VEGF medications may benefit from treatment with new and potent anti-VEGF molecules such as brolucizumab and faricimab [ 25 , 26 ]. Long-term, chronic, untreated DME appears to develop resistance and a poor treatment response to routine antiangiogenetic drugs in general, according to studies [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Elnahry et al found that OCT and OCT-angiography markers, such as a higher CSFT and a smaller foveal avascular zone area, as well as increased vessel densities in superficial parafovea and deep fovea, were associated with a better response to monthly intravitreal bevacizumab injections than in non-responders [ 24 ]. Patients who do not respond adequately to standard anti-VEGF medications may benefit from treatment with new and potent anti-VEGF molecules such as brolucizumab and faricimab [ 25 , 26 ]. Long-term, chronic, untreated DME appears to develop resistance and a poor treatment response to routine antiangiogenetic drugs in general, according to studies [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term, chronic, untreated DME appears to develop resistance and a poor treatment response to routine antiangiogenetic drugs in general, according to studies [ 27 , 28 ]. These eyes can also be treated with potent anti-VEGF molecules like faricimab [ 26 ]. Corticosteroid therapy, which controls the crucial role of inflammation in DME, is used to treat persistent, chronic DME [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intravitreal injection of anti-vascular endothelial growth factor (VEGF) agents has been regarded as the gold standard treatment as the rst option for center-involving DME (CI-DME) (2). However, in some cases of DME, the treatment with anti-VEGF agents tends to be unsatisfactory (3). Thus, research for more satisfactory treatment options pursues.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, by exclusively targeting VEGF, there is an unmet need for anti-VEGF sub-responsive patients. 16 Some can be treated with cortico-steroid implants; however, these have a higher side effects profile such as development of cataract and glaucoma. In this direction, the role of the Ang/Tie pathway has been investigated with promising results for the treatment of DME.…”
mentioning
confidence: 99%
“…The burden of such frequent injection intervals and associated cost have driven efforts to study other alternative molecular pathways as possible new treatment targets. Additionally, by exclusively targeting VEGF, there is an unmet need for anti‐VEGF sub‐responsive patients 16 . Some can be treated with cortico‐steroid implants; however, these have a higher side effects profile such as development of cataract and glaucoma.…”
mentioning
confidence: 99%